Understanding Youth Athlete Motivation, Training, and Activity Progression During and After the COVID-19 Sports Interruption - Elliot Greenberg; Eric Greenberg; J. Todd Lawrence; Theodore Ganley (International Journal of Sports Physical Therapy)
# Background